The Influence of Psychological Empowerment on Work Engagement with The Mediating Role of Organizational Commitment in Wera Community Health Center Employees - Herdiman Herdiman; Susanto Tirtoprojo (International Journal of Management Science and Information Technology, 2024)
This research aims to analyze the effect of psychological empowerment on work engagement with organizational commitment as a mediating variable. The method used in this research is a quantitative method with a survey approach. Data was collected from 99 employees of the Wera District Health Center, Bima Regency, taken from the entire population using a saturated sampling technique. Data analysis was carried out using SmartPLS to test the relationship between the variables studied. The research results show that psychological empowerment positively and significantly affects work engagement. In addition, organizational commitment has been shown to mediate between work engagement and psychological empowerment. These findings indicate that employee psychological empowerment can increase work engagement and organizational commitment. This research shows that organizational leaders need to prioritize employee psychological empowerment as part of a strategy to increase work engagement. Training and development programs centered on psychological empowerment and organizational commitment can be effective interventions. The next research is to conduct a longitudinal study to observe how psychological empowerment impacts work engagement over time. Additionally, expanding the sample size and examining other factors that may influence work engagement could provide a more comprehensive understanding of these dynamics across various organizational contexts.